2017
DOI: 10.1002/ls.1382
|View full text |Cite
|
Sign up to set email alerts
|

First principles study of organophosphorus additives in boundary lubrication conditions: Effects of hydrocarbon chain length

Abstract: We apply first principle calculations to investigate the effects of the hydrocarbon chain length in additive molecules under boundary lubrication conditions. In these conditions, occurring in high‐pressure applications, the thickness of the oil film becomes extremely thin, and the additive molecules remain confined between the two solid surfaces in contact. We consider two types of organophosphorous additives having the same phosphite group but hydrocarbon chains of different lengths. By comparing the molecula… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
28
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 20 publications
(28 citation statements)
references
References 59 publications
(109 reference statements)
0
28
0
Order By: Relevance
“…Ab initio MD simulations of trimethyl phosphite and tributyl phosphite confined and sheared between Fe(110) slabs showed that dissociation of both molecules proceeded along the same pathway at high load, but that more phosphorous was likely to be released with the smaller molecule because of the greater number of adsorbed molecules per unit area. 22,30 It was further shown that the energy of dissociation adsorption decreased as the number of detached methoxy groups increased. 31 Lastly, reactive MD simulations compared TCP with four alkyl phosphates (primary linear, primary branched, secondary, and tertiary).…”
Section: Introductionmentioning
confidence: 99%
“…Ab initio MD simulations of trimethyl phosphite and tributyl phosphite confined and sheared between Fe(110) slabs showed that dissociation of both molecules proceeded along the same pathway at high load, but that more phosphorous was likely to be released with the smaller molecule because of the greater number of adsorbed molecules per unit area. 22,30 It was further shown that the energy of dissociation adsorption decreased as the number of detached methoxy groups increased. 31 Lastly, reactive MD simulations compared TCP with four alkyl phosphates (primary linear, primary branched, secondary, and tertiary).…”
Section: Introductionmentioning
confidence: 99%
“…Figure e,d shows the P and S elements appearing on the surface of wear are coming from P 888P DOSS. Besides the BEs of these elements are completely different from those of neat ILs indicating the formation of phosphorus or sulfur products decomposed from P 888P DOSS under rigorous condition, and then reacted with new born Mg surface to form a novel antiwear agent …”
Section: Resultsmentioning
confidence: 99%
“…29 The calculations showed that the mechanisms (a), (b), and (c) described above all have at least one exothermic reaction pathway. 29 In addition to static calculations, ab initio molecular dynamics (AIMD) simulations have also been used to investigate the dissociation of tri(methyl)phosphate, 30 tri(methyl)phosphite, 31 and tri(nbutyl)phosphite 32 confined between iron surfaces where load and sliding are applied. The AIMD simulations have given insight into the dissociation pathways of organophosphorus molecules inside tribological contacts.…”
Section: Introductionmentioning
confidence: 99%